Food Price Control Strategy in Bogor Regency - Wulandari, Sally; Sutrisno, Edy (International Journal of Economics Development Research (IJEDR), 2025)
The volatility of global food prices has increasingly impacted developing countries, including Indonesia, which remains vulnerable due to its dependence on imported commodities. In Bogor Regency, rapid urbanization and the conversion of agricultural land have further exacerbated food price instability. This study aims to assess the effectiveness of food price control strategies implemented by the Bogor Regency Government, focusing on inflationary pressures arising from both cost-push and demand-pull factors. The research employs a qualitative descriptive method, combining secondary data from literature reviews with primary data collected through in-depth interviews and documentation from key stakeholders, including local government agencies, market authorities, and central institutions. The findings reveal that although several programs—such as the Mobile Food Market (Gerakan Pangan Murah), food reserve management, and market interventions—have been implemented, significant challenges remain in infrastructure, inter-agency coordination, and public awareness. This study highlights the strategic roles of the Food Security Agency, the Department of Trade and Industry, Bank Indonesia, the Central Statistics Agency (BPS), and law enforcement in maintaining food price stability. Through the implementation of the 4K Strategy—Affordability, Supply Availability, Smooth Distribution, and Effective Communication—Bogor Regency has the potential to develop a more resilient food system capable of withstanding both supply- and demand-side shocks. The study concludes that a comprehensive and collaborative approach is essential for managing food inflation sustainably. Key recommendations include enhancing inter-agency synergy through regular coordination forums, strengthening local food production through agricultural innovation and farmer support, developing distribution infrastructure such as road networks and cold storage facilities, and expanding mobile food market programs and public education on smart food consumption. These measures are crucial to ensure that food remains affordable and accessible to all segments of society, particularly vulnerable groups, while also reinforcing the region's economic resilience.